Synthesis of polycalciumphenylsiloxane and composites based on the skeleton of a sea urchin with the resulting polymer - Nikolai Р. Shapkin; Irina G. Khalchenko; Kvan H. Kim; Evgeniy K. Papynov; Alexander N. Fedorets; Natalia V. Maslova; Michael I. Balanov (Chimica Techno Acta)
In this work, we obtained polycalciumphenylsiloxane (PCPS) by the interaction of calcium bis (acetylacetonate) with polyphenylsiloxane. The first method consisted in boiling the starting reagents in toluene for several hours; the second was as follows: the mixture of the starting reagents was preliminarily treated mechanically in a ball mill, followed by boiling in toluene for several hours. Two fractions, soluble and insoluble, were isolated in both syntheses. They were investigated using IR, NMR spectroscopy, thermogravimetric analysis, and gel permeation chromatography. It was shown that the insoluble fraction is a mixture of calcium acetylacetonate and polyphenylsiloxane with a small calcium ion content. The soluble fraction is polycalciumphenylsiloxane. The yield of the soluble fraction is higher in the second synthesis method. The polymers obtained in the first and second synthesis methods are similar in composition and structure, which was confirmed by physicochemical methods. Next, the skeleton of the sea urchin Strongylocentrotus intermedius was treated with a soluble fraction in toluene. In this case, a composite was obtained, which was treated with 2–3% hydrochloric acid and then calcined at a temperature of 600 °C. At each stage, the composition of the composites was investigated using elemental analysis and IR spectroscopy. The morphology was investigated using scanning electron microscopy.